Analisis Kemampuan Literasi Digital Pada UMKM di Kota Tasikmalaya (Studi Kasus: PapaBurjo) - Devina Fauziyah; Adam Hermawan; Asep Nuryadin (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to analyze the digital literacy skills of PapaBurjo MSMEs as a case study to understand the extent to which MSMEs in Tasikmalaya City have utilized digital technology in running their business. The background to this research is based on the importance of digital literacy in increasing the competitiveness of MSMEs in the digital era and the potential of MSMEs in Tasikmalaya City. Through a qualitative approach, this research describes the digital literacy skills that PapaBurjo has applied in the Information and Data Literacy, Communication and Collaboration, Digital Content Creation, Safety, and Problem Solving competencies; as well as the positive impact that PapaBurjo has had on digital literacy. The research results show that PapaBurjo has a fairly good basic digital literacy, especially in terms of creating digital content and solving problems. However, there are still several aspects that need to be improved, such as the evaluation of information and the use of technology for public services, the risks and threats of cyber crime, as well as the use of digital technology to innovate and develop digital competencies. Digital literacy has had a significant positive impact on PapaBurjo's business development. The ability to utilize digital platforms and digital marketing strategies has contributed to increasing profits and expanding business reach and has facilitated PapaBurjo in building a wider business network and attracting the interest of potential business partners and investors.